2020
DOI: 10.1155/2020/3864571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Workplace-Related Factors on the Prevalence of Fibromyalgia among Israeli Kindergarten Teachers

Abstract: Background. Fibromyalgia syndrome (FMS), a chronic widespread pain disorder, has been associated with various models of stress, including those that are workplace-related. In a previous study, we have documented the significantly increased prevalence of FMS among schoolteachers, as well as correlating symptoms with stressful workplace-related factors. In the current study, we have focused on the specific population of kindergarten teachers and attempted to document both the prevalence of FMS symptoms among thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Askin et al reported a higher prevalence of FM symptoms among cardiac patients using the Fibromyalgia Impact Questionnaire and VAS scale for pain, finding 22 symptoms in 62 patients versus 4 in normal subjects (16). Y. Muskila's study on gender differences in FM incidence included 321 individuals and reported a higher incidence in women (11.4%) compared to men (1.5%) (17). Caroline et al's large-scale study investigated pain incidence rates among FM and non-FM individuals, noting a higher prevalence of FM symptoms in women and more medical problems in men (18).…”
Section: Discussionmentioning
confidence: 99%
“…Askin et al reported a higher prevalence of FM symptoms among cardiac patients using the Fibromyalgia Impact Questionnaire and VAS scale for pain, finding 22 symptoms in 62 patients versus 4 in normal subjects (16). Y. Muskila's study on gender differences in FM incidence included 321 individuals and reported a higher incidence in women (11.4%) compared to men (1.5%) (17). Caroline et al's large-scale study investigated pain incidence rates among FM and non-FM individuals, noting a higher prevalence of FM symptoms in women and more medical problems in men (18).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of FM in the general population ranges from 0.2% to 6.6%, with higher rates among women (2.4-6.8%) [12]. The prevalence of FM symptoms among female teachers in Israel was 11.4%, significantly higher than the rate among male teachers (1.5%) [13]. While the exact etiology of FM remains unclear, trauma is recognized as a significant risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have proved that anxiety is highly related to chronic diseases [14][15][16] and subhealth [17,18] of early childhood teachers, such as cardiovascular diseases, gastric ulcer [19] and frequent colds [20] . Anxiety also has a negative impact on the occupational stability of early childhood teachers [21] .…”
Section: Introductionmentioning
confidence: 99%